Experimental philosophy and armchair philosophy - Srinivasan, AP (2009)
Experimental Philosophers argue that the credibility of armchair methodology is undermined by recent empirical findings that show that people's intuitive judgments about thought experiments vary systematically with a host of factors, such as cultural or socioeconomic background. In this thesis, I argue that the experimentalists’ sceptical challenge (ESC) must be understood and evaluated as a philosophical—specifically epistemological—claim, and not as (experimental philosophers maintain) a “merely methodological” claim. To that end, I (1) summarize the findings of experimental philosophy, (2) articulate a formalization of ESC on behalf of experimental philosophers, (3) distinguish ESC from traditional forms of scepticism, and explain why traditional responses to intuition scepticism fail to adequately address it; (4) argue that ESC suffers from a threat of incoherence, drawing on results of a survey on people’s meta-intuitions about the significance of divergence; (5) suggest that the proponent of ESC, in defending the coherence of his own position, opens up the possibility of parallel defences on behalf of armchair philosophy; and (6) lay out possible epistemological considerations that the armchair philosopher can use to defend her traditional methodology against the experimentalist’s challenge.